Child-Parent Communication to Form Islamic Character - Afiah Najikhah; Dzulfikar Akbar Romadlon (Indonesian Journal of Cultural and Community Development, 2022)
Communication is very important for human life. In addition to interacting, communication is also used as a medium in delivering information and a tool to persuade others. Communication is usually done and starts from the smallest scope, namely the family. Through communication, parents in the family can influence other members, especially children. Communication that is carried out continuously by parents to children can also form habits that are spontaneously carried out by children so that they can create qualitative research with data collection techniques in the form of interviews, observations, and documentation and the formation of characters according to the wishes of parents. how to communicate between parents and children so as to create a behavior that forms a character in the future. The purpose of this study is to determine the form of parent-child communication, how parents shape the child's Islamic character, and the success of parent-child communication. This research was conducted in Randubango Village, Mojosari District. In this study, the author uses a phenomenological approach. This study involved ten parents and ten children as informants. The researcher also asked several questions which included how communication occurs between parents and children, how parents build Islamic character towards their children, and how successful parent-child communication is in building Islamic character in Randubango Village, Mojosari District. The results of the study show that: First, The form of parent-child communication is done through conversation, intimate interaction, and evaluation. Second, the method of forming the Islamic character of children in Randubango Village, Mojosari District is carried out through conversation, reading stories of inspirational figures, exemplary from both parents and habituation. Third, for the success of parent-child communication, namely with an open attitude, and mutual trust.